Rapid Re-Infection with Soil-Transmitted Helminths after Triple-Dose Albendazole Treatment of School-Aged Children in Yunnan, People's Republic of China - Yap, Peiling (The American Society of Tropical Medicine and Hygiene, 2013)
Post-treatment soil-transmitted helminth re-infection patterns were studied as part of a randomized controlled trial among school-aged children from an ethnic minority group in Yunnan province, People's Republic of China. Children with a soil-transmitted helminth infection (N = 194) were randomly assigned to triple-dose albendazole or placebo and their infection status monitored over a 6-month period using the Kato-Katz and Baermann techniques. Baseline prevalence of Trichuris trichiura, Ascaris lumbricoides, hookworm, and Strongyloides stercoralis were 94.5%, 93.3%, 61.3%, and 3.1%, respectively, with more than half of the participants harboring triple-species infections. For the intervention group (N = 99), the 1-month post-treatment cure rates were 96.7%, 91.5%, and 19.6% for hookworm, A. lumbricoides, and T. trichiura, respectively. Egg reduction rates were above 88% for all three species. Rapid re-infection with A. lumbricoides was observed: the prevalence 4 and 6 months post-treatment was 75.8% and 83.8%, respectively. Re-infection with hookworm and T. trichiura was considerably slower.